Recensione a The Reception of Husserlian Phenomenology in North America: Ed: Michela Beatrice Ferri In collaboration with Carlo Ierna, “Contributions to Phenomenology. In Cooperation with the Center for Advanced Research in Phenomenology”, vol. 100, Springer, Cham (CH) 2019, pp. XXVII-482. Paperback 103,99. E-book 83,29. (Materiali di Estetica. Terza serie, 2020)
-